STRATEGI KOMUNIKASI DEPARTEMENT PRODUKSI DALAM MENINGKATKAN KUALITAS PROGRAM PESONA INDONESIA PADA TVRI DKI JAKARTA (Jurnal Ilmu Komunikasi, 2024)
This study aims to find out and describe how the Communication Strategy of the Production Department in Improving the Quality of the Pesona Indonesia Program at TVRI DKI Jakarta. With this communication strategy, communication planning can be achieved in accordance with organizational management. On television stations in packaging quality programs and worthy of being aired on television. The method used in this study is qualitative descriptive method. The data used in this study are primary data and secondary data. Primary data is in the form of direct interviews without intermediaries with several informants. While secondary data is in the form of supporting data from primary data such as journals, books. The theory used in this study is the theory of strategy & communication planning according to George R.Terry with a POAC management approach, namely: Planning, Organizing, Actuating (controlling/implementing), and Controlling. The results of this study are concluded in the Pesona Indonesia program there is a program planning strategy which discusses how the strategy so that Pesona Indonesia experiences rating and share, strategies in improving program quality, brainstorming strategies, pre-production strategies, production strategies, post-production strategies are in accordance with the theoretical analysis used by strategy theory & communication planning.